Green synthesis, characterization, photocatalytic and antibacterial activities of copper oxide nanoparticles of copper oxide nanoparticles - Saeid Taghavi Fardood; Ferzaneh Moradnia; Siamak Heidarzadeh; Ali Naghipour (Nanochemistry Research, 2023)
In this work, copper oxide nanoparticles were efficiently synthesized using a simple and environmentally friendly sol-gel process and studied their degradability of reactive blue 21 dye and antibacterial properties. To characterize the synthesized CuO nanoparticles, powder X-ray diffraction (XRD), Brunauer Emmett Teller (BET), transmission electron microscope (TEM), field emission scanning electron microscopy (FESEM), and Differential reflectance spectroscopy (DRS) analysis were used. The particle size was determined using the TEM technique to be roughly 25 nm. The optical band gap of CuO nanoparticles was calculated using the Tauc relation from the absorption spectra and was determined to be about 2.04 eV. The CuO NPs showed good photocatalysis activity towards the Reactive Blue 21 dye as an organic pollutant so that 86% of RB21 was removed in 60 min in room condition and visible light region. CuO NPs were evaluated for antibacterial efficacy against including Gram negative (Escherichia coli, Salmonella typhimurium, Proteus mirabilis, Pseudomonas aeruginosa) and Gram positive (Staphylococcus aureus, Enterococcus faecalis) bacteria.